Autophagy regulation of virus infection in aquatic animals - Chen Li; Yunli Zhang; Xianliang Zhao; Li Li; Xianghui Kong (Reviews in Aquaculture, 2023)
Autophagy is a conserved intracellular degradation process that is required to maintain host homeostasis and cope with invading pathogens. Over the past few decades, studies on mammals have greatly increased our understanding of the relationship between autophagy and virus infection. Autophagy may convey the invader to lysosomes to degrade or activate the host immune response against virus replication. However, many viruses have developed some strategies that evade the degradative nature of autophagy or hijack this pathway for their gain. It follows that autophagy during viral infection is a double‐edged sword. In contrast to mammals, the review on autophagy modulated by the aquatic animal virus is limited. Here, after a brief description of the main information about autophagy, we highlight current progress on the interplays between autophagy and virus infection in aquatic animals, including the phenomenon of autophagy upon virus infection, the effect of modulating autophagy on virus replication, and the crosstalk between autophagy and immune response during virus infection. This review will help us better understand the pathogenic mechanism of aquatic animal viruses and develop proper antiviral countermeasures aimed at modulating autophagy.